Application of ultrasound‐guided seminal vesicle radiography combining CT three‐dimensional reconstruction technique in transurethral seminal vesiculoscopy. (14th October 2020) - Pang, Kun; Lou, Kexin; Huang, Yayong; Wang, Hao; Hao, Lin; Shi, Zhenduo; Zang, Guanghui; Wei, Cui; Chen, Bo; Han, Conghui
Abstract: For the treatment of ejaculatory duct obstruction, transurethral seminal vesiculoscopy (TSV) is the most common method, but the success rate is much lower than studies that have reported. So we developed a new ultrasound‐guided seminal vesicle radiography (UGSVR) combining CT three‐dimensional reconstruction (CT‐TR) technique to improve the success rate of TSV. Between June 2018 and November 2019, 32 patients were enrolled and randomly assigned to two groups: experimental group (UGSvR combining CT‐TR) and control group (standard evaluation). Baseline information, including age, smoking history and body mass index (BMI), was compared preoperatively. Surgical parameters included success rates (SR), surgical time (ST), catheter days (CD), length of hospital stays (HS) and complications were compared between groups. There were no statistically significant differences in baseline data between the two groups (all p  > .05). There were no significant differences in the CD, HS and complications between the two groups (all p  > .05), but the differences in ST and SR were statistically significant ( p  < .05). In conclusion, this new technique of UGSvR combining CT‐TR was achieving a satisfactory increase in the success rate of TSV, while not increasing the incidence of complications, compared to normal evaluation before TSV operation.